Hybrid Nd:YAG/Nd:LuAG Nanosecond Laser Oscillator and Amplifier - Lei, Xinxing; Fu, Xing; Liu, Qiang (Frontiers in Physics, 2022)
We demonstrate an active mirror Q-switched laser with Nd:YAG/Nd:LuAG hybrid gain media, achieving a laser output of 1 J, 10 Hz, 8 ns. Using this hybrid oscillator as well as Nd:YAG and Nd:LuAG amplifiers, the difference in extraction efficiency of hybrid amplification was measured and analyzed, which is useful for high energy hybrid amplification chains.